IMPACT MODEL OF SOME FACTORS ON ORGANIZATIONAL PERFORMANCE - Phong, Vo Tan; Tuyet, Mai Thi Anh; Ly, Do Van (PEOPLE: International Journal of Social Sciences, 2024)
This research explores the effects of human resource management practices, organizational culture, organizational innovation, and intellectual capital on organizational performance, with a focus on enterprises in Vietnam. Utilizing foundational theories such as the Resource-Based View and Dynamic Capability Theory, the study integrates these elements to provide a comprehensive understanding of their combined impact. The methodology employs Structural Equation Modeling to analyze data collected from representative firms, ensuring robust insights. Findings demonstrate that human resource management practices significantly influence employee satisfaction and productivity, while an innovation-oriented organizational culture enhances adaptability and creativity. Furthermore, investment in intellectual capital drives competitive advantage, and organizational innovation directly contributes to improved performance outcomes. These results offer critical implications for both academic research and practical applications, providing strategies for business leaders to enhance operational effectiveness and sustain competitive performance in dynamic markets.